Distribution of MED12 mutations in fibroadenomas and phyllodes tumors of the breast: implications for tumor biology and pathological diagnosis - Pfarr, Nicole; Kriegsmann, Mark; Sinn, Peter; Endris, Volker; Herpel, Esther; Muckenhuber, Alexander; Jesinghaus, Moritz; Penzel, Roland; Weichert, Wilko; Stenzinger, Albrecht (Genes, chromosomes & cancer, 2015)
Somatic mutations in exon 2 of MED12 have been described in benign and malignant smooth muscle cell tumors suggesting a functional role in these neoplasms. Recently fibroadenomas of the breast were also reported to harbor MED12 mutations. Hence, we explored MED12 mutations in fibroepithelial tumors of the breast, histological subtypes of fibroadenomas and phyllodes tumors, to validate and extend previous efforts. Using conventional Sanger sequencing, we profiled 39 cases of fibroepithelial breast tumors comprising classic histological subtypes of fibroadenomas as well as benign and malignant phyllodes tumors for mutations in exon 2 of MED12. MED12 mutations were detected in 60% of all tumor samples with the majority being missense mutations affecting codon 44. Additionally, we report novel in-frame deletions that have not been described previously. Sixty-two percent of the fibroadenomas harbored mutated MED12 with intracanalicular fibroadenomas being the most frequently mutated histological subtype (82%). Of note, 8/11 of benign phyllodes tumors had MED12 mutations while only 1/5 of malignant phyllodes tumors showed mutations in exon 2 of MED12. In conclusion, we confirm the frequent occurrence of MED12 mutations in fibroadenomas, provide evidence that most intracanalicular fibroadenomas closely resembling benign phyllodes as well as benign phyllodes tumors harbor MED12 mutations, and conclude that MED12 mutations in malignant phyllodes tumors appear to be relatively rare. © 2015 Wiley Periodicals, Inc.
Gesehen am 11.04.2017